2021
DOI: 10.1007/s11356-021-14427-y
|View full text |Cite
|
Sign up to set email alerts
|

Nanoencapsulation of thyme essential oil: a new avenue to enhance its protective role against oxidative stress and cytotoxicity of zinc oxide nanoparticles in rats

Abstract: Although the green synthesis of nanometals is eco-friendly, the toxicity or safety of these biosynthesized nanoparticles in living organisms is not fully studied. This study aimed to evaluate the potential protective role of encapsulated thyme oil (ETO) against zinc oxide nanoparticles (ZnO-NPs). ETO was prepared using a mixture of whey protein isolate, maltodextrin, and gum Arabic, and ZnO-NPs were synthesized using parsley extract. Six groups of male Sprague-Dawley rats were treated orally for 21 days which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 109 publications
1
1
0
Order By: Relevance
“…The results of the GC-MS analysis of Thymus capitatus EO revealed the presence of 13 different compounds belonging to the phenolic and terpenic groups (Table 2). Similar results have been reported by Hassan et al [33]. Moreover, previous studies have indicated that the major component of thyme oil is carvacrol [34].…”
Section: Composition Of Thyme Essential Oilssupporting
confidence: 91%
“…The results of the GC-MS analysis of Thymus capitatus EO revealed the presence of 13 different compounds belonging to the phenolic and terpenic groups (Table 2). Similar results have been reported by Hassan et al [33]. Moreover, previous studies have indicated that the major component of thyme oil is carvacrol [34].…”
Section: Composition Of Thyme Essential Oilssupporting
confidence: 91%
“…However, the use of large-scale TPO is not feasible due to the hydrophobicity and volatility of the bioactive components of the oil (Esmaeili & Asgari, 2015 ). Thus, previous studies reported several attempts at incorporating the oil into different delivery systems (Mansouri et al., 2021 ; Almasi et al., 2021 ; Upadhyay et al., 2021 ; Hassan et al., 2021 ; Al-otaibi, 2021 ). A lot of attention has been focused on the use of nano-emulsions to deliver the oils by forming water-based products so as to enhance the solubility of the insoluble components (Donsì & Ferrari, 2016 ).…”
Section: Introductionmentioning
confidence: 99%